2008
DOI: 10.1111/j.1095-8649.2008.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of growth in larval cohorts of the Japanese sardine Sardinops melanostictus in a coastal nursery area

Abstract: Growth patterns of larval sardine Sardinops melanostictus were studied in a coastal nursery area, in southern Japan for four monthly hatch cohorts of larvae (November, December, January and February) for the 2003-2004 and 2004-2005 seasons. Laird-Gompertz models were fitted to each cohort using both total length (L T )-at-age at capture and mean L T -at-age data derived from backcalculations. In both approaches, the absolute daily growth rates (G R ) and absolute daily growth rates at the inflection point (G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This result showed that fish size can be estimated using the otolith size and also that individual growth patterns of juveniles backcalculated using the biological intercept method were reliable. Proportional relationships between fish size and otolith size have also been reported in different species of salmon, e.g., Salmo salar (Wright et al, 1990;Carreño, 2010), Oncorhynchus keta (Fukuwaka, 1998), Oncorhynchus tshawytscha (Neilson & Geen, 1982) and other teleost species, i.e., Fundulus heteroclitus (Radtke & Dean, 1982), Engraulis ringens (Hernandez & Castro, 2000); Sebastes inermis (Plaza et al, 2001), Sardinops melanostictus (Plaza et al, 2008). In some cases absence of proportionality have also been observed (decoupling), but mainly in extreme conditions of both feeding and temperature (Mosegaard et al, 1988;Hare & Cowen, 1995;Baumann et al, 2005).…”
Section: Characterization Of Otolith Microstructurementioning
confidence: 82%
“…This result showed that fish size can be estimated using the otolith size and also that individual growth patterns of juveniles backcalculated using the biological intercept method were reliable. Proportional relationships between fish size and otolith size have also been reported in different species of salmon, e.g., Salmo salar (Wright et al, 1990;Carreño, 2010), Oncorhynchus keta (Fukuwaka, 1998), Oncorhynchus tshawytscha (Neilson & Geen, 1982) and other teleost species, i.e., Fundulus heteroclitus (Radtke & Dean, 1982), Engraulis ringens (Hernandez & Castro, 2000); Sebastes inermis (Plaza et al, 2001), Sardinops melanostictus (Plaza et al, 2008). In some cases absence of proportionality have also been observed (decoupling), but mainly in extreme conditions of both feeding and temperature (Mosegaard et al, 1988;Hare & Cowen, 1995;Baumann et al, 2005).…”
Section: Characterization Of Otolith Microstructurementioning
confidence: 82%
“…For larvae, growth was significantly explained by Laird‐Gompertz models, which is expected for most clupeoids (Plaza et al . , ; Takahashi et al ., ; Watanabe & Saito, ). Similar allometric patterns were also well explained by Laird‐Gompertz models for pre‐recruits and recruits.…”
Section: Discussionmentioning
confidence: 97%
“…Freitas et al (2009) determined size after hatching around 7.2 mm for larvae of Odontesthes argentinensis (Valenciennes, 1835). The LairdeGompertz model has been successfully used to describe larval and juvenile growth of marine fishes (Dul ci c and Kraljevic, 1996;Plaza et al, 2008;Brown and S anchez, 2010) The LairdeGompertz model explained properly the growth in length for Odontesthes nigricans juveniles because an asymptotic trend was detected for larger specimens. According to the model, SL ∞ was 72.4 mm, resulting lower than 85.4 mm established by Powles and Sandeman (2008) for juveniles of Labidesthes sicculus (Cope, 1865), a north American silverside.…”
Section: Discussionmentioning
confidence: 98%